Long Non-coding RNAs in Gammaherpesvirus Infections: Their Roles in Tumorigenic Mechanisms - Liu, Wen; Zhang, Yan; Luo, Bing (Frontiers in Microbiology, 2021)
Long non-coding RNAs (lncRNAs) regulate gene expression at the epigenetic, transcriptional or post-transcriptional level by interacting with protein, DNA, and RNA. Emerging evidence suggests that various lncRNAs are abnormally expressed and play indispensable roles in viral-triggered cancers. Besides, a growing number of studies have shown that virus-encoded lncRNAs participate in tumorigenesis. However, the functions of most lncRNAs in tumors caused by oncogenic viruses and their underlying mechanisms remain largely unknown. In this review, we summarize current findings regarding lncRNAs involved in cancers caused by Epstein-Barr virus (EBV) and Kaposi's sarcoma herpesvirus (KSHV). Additionally, we discuss the contribution of lncRNAs to tumor occurrence, development, invasion, and metastasis; the roles of lncRNAs in key signaling pathways and their potential as biomarkers and therapeutic targets for tumor diagnostics and treatment.